Respuesta :
Answer:
[tex](5,-24)[/tex] and [tex](3,-12)[/tex]
Step-by-step explanation:
we have
[tex]y=-x^{2} +2x-9[/tex] -----> equation A
[tex]y=-6x+6[/tex] -----> equation B
equate the equation A and equation B
[tex]-x^{2} +2x-9=-6x+6[/tex]
[tex]-x^{2} +2x-9+6x-6=0[/tex]
[tex]-x^{2} +8x-15=0[/tex]
The formula to solve a quadratic equation of the form [tex]ax^{2} +bx+c=0[/tex] is equal to
[tex]x=\frac{-b(+/-)\sqrt{b^{2}-4ac}} {2a}[/tex]
in this problem we have
[tex]-x^{2} +8x-15=0[/tex]
so
[tex]a=-1\\b=8\\c=-15[/tex]
substitute in the formula
[tex]x=\frac{-8(+/-)\sqrt{8^{2}-4(-1)(-15)}} {2(-1)}[/tex]
[tex]x=\frac{-8(+/-)\sqrt{64-60}} {-2}[/tex]
[tex]x=\frac{-8(+/-)2}{-2} [/tex]
[tex]x=\frac{-8+2}{-2}=3[/tex]
[tex]x=\frac{-8-2}{-2}=5[/tex]
Find the values of y
For [tex]x=3[/tex]
[tex]y=-6x+6[/tex] ------> [tex]y=-6(3)+6=-12[/tex]
For [tex]x=5[/tex]
[tex]y=-6x+6[/tex] ------> [tex]y=-6(5)+6=-24[/tex]
The solutions are the points [tex](3,-12)[/tex] and [tex](5,-24)[/tex]